2008
DOI: 10.1128/jvi.01681-07
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Cyclin-Dependent Kinases at the Beginning of Human Cytomegalovirus Infection Specifically Alters the Levels and Localization of the RNA Polymerase II Carboxyl-Terminal Domain Kinases cdk9 and cdk7 at the Viral Transcriptosome

Abstract: We previously reported that defined components of the host transcription machinery are recruited to human cytomegalovirus immediate-early (IE) transcription sites, including cdk9 and cdk7 (S. Tamrakar, A. J. Kapasi, and D. H. Spector, J. Virol. 79:15477-15493, 2005). In this report, we further document the complexity of this site, referred to as the transcriptosome, through identification of additional resident proteins, including viral UL69 and cellular cyclin T1, Brd4, histone deacetylase 1 (HDAC1), and HDAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 51 publications
3
70
0
Order By: Relevance
“…This modification is associated with changes in the abundance, activity, and localization of cdk9 and cdk7, as shown previously by S. Tamrakar et al (40). This same group has also shown that the addition of cdk inhibitors at the start of infection alters the levels and localization of cdk9 and cdk7 (15). More recently, the Kaposi's sarcoma-associated herpesvirus K-cyclin protein has been shown to interact with cdk9 (6).…”
supporting
confidence: 49%
“…This modification is associated with changes in the abundance, activity, and localization of cdk9 and cdk7, as shown previously by S. Tamrakar et al (40). This same group has also shown that the addition of cdk inhibitors at the start of infection alters the levels and localization of cdk9 and cdk7 (15). More recently, the Kaposi's sarcoma-associated herpesvirus K-cyclin protein has been shown to interact with cdk9 (6).…”
supporting
confidence: 49%
“…Thus, it was not surprising to find that UL69 binds to RNA nonspecifically, but what was surprising was that this ability to bind RNA was not required for UL69-mediated nuclear RNA export (187). However, the recent finding of UL69 localization to sites of viral gene expression (86) indicates that UL69 selects viral mRNAs for export because it accumulates at subnuclear sites where viral transcripts are synthesized. This mechanism may also explain why UL69 stimulates the expression of reporter constructs that contain an simian virus 40 intron (201).…”
Section: Ppul69mentioning
confidence: 86%
“…While several studies have localized IE transcription to the viral transcriptosomes, which are subnuclear foci that contain the input viral genome as well as several cellular transcription factors, cyclin-dependent kinases, and RNAP II that form adjacent to POD/ND10 structures (24,25,30,57), the site of viral late gene transcription has not been established, although it has been hypothesized to occur around the replication center, given the localization of phosphorylated RNAP II there at later times of infection (57). We have further identified H3K4 and newly labeled BrU transcripts to localize outside the viral replication center, further indicating the perireplication center region to be transcriptionally active.…”
Section: Discussionmentioning
confidence: 99%